Pembangunan Sumber Daya Sentralisasi Data pada Aplikasi Pengelolaan UMKM Menggunakan RESTFul dan Oauth 2.0 - Setiyawati, Nina; Bangkalang, Dwi Hosanna; Asmara, Gilang Windu (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Services for Micro, Small and Medium Enterprises (MSMEs) continue to be improved by the Department of Cooperatives, Small and Medium Enterprises (DinKopUKM) of Salatiga City. One way is to implement technology in various services. These applications need to be supported by the principle of information integration so that there is no data redundancy and dissemination of valid and reliable data is achieved. In this research, a resource server was built using RESTFul which allows third party systems to connect to product components to query information about objects and perform basic operations using the HTTP protocol. And using Oauth 2.0 is an open authorization protocol that allows third-party systems or applications via the HTTP protocol to access resources with certain access rights. This system is divided into four main parts, namely MSME actors registered in the system as resource owners, third party applications as data requesters/recipients, resource servers as resource service providers, and authorization servers which are useful for validating the identity of users and third party applications. With an integrated system, MSME players in the city of Salatiga do not need to repeat the MSME data collection process when using other information systems provided by the Salatiga city government while maintaining the security and privacy of user data.